Multidisciplinary approach to dysphagia: literature review and clinical perspectives - Barrón Cervantes, Natalia M. (2025)
Dysphagia is defined as an alteration in the swallowing process, which is divided into two phases: oropharyngeal and esophageal. Identifying the location of the disorder is essential for guiding the diagnostic evaluation. Oropharyngeal dysphagia is mainly associated with chronic neurological diseases, as well as structural causes such as Zenker’s diverticulum, certain neoplasms, or medication-related factors. Esophageal dysphagia, on the other hand, may result from obstruction (strictures, Schatzki rings, cancer), motility disorders (achalasia, distal esophageal spasm), or inflammatory processes, with gastroesophageal reflux disease and eosinophilic esophagitis being the most common causes. The initial clinical assessment, based on symptoms, helps guide further diagnostic studies. If oropharyngeal dysphagia is suspected, laryngoscopy should be performed and the patient referred to an otolaryngologist or a speech-language pathologist. In cases of suspected esophageal dysphagia, endoscopy and esophagography are recommended. Impedance pH monitoring, manometry, and computed tomography are indicated when specific diagnoses are suspected.